PENGARUH SELF ESTEEM DAN SELF REGULATION TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Fitriani Nur; Andi Kastiar Latief (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
The research aims to: 1) describe the Self Esteem of the eleventh grade students of Senior Islamic High School Guppi of Samata, Gowa regency; 2) describe the Self Regulation of the eleventh grade students of Senior Islamic High School Guppi of Samata, Gowa regency,3) find out the students’ Mathematic learning outcome of the eleventh grade students of Senior Islamic High School Guppi of Samata, Gowa regency, 4) find out the effect of Self Esteem on the students’ Mathematic learning outcome of the eleventh grade students of Senior Islamic High School Guppi of Samata, Gowa regency, 5) to find out the effect of Self regulation on the students’ Mathematic learning outcome of the eleventh grade students of Senior Islamic High School Guppi of Samata, Gowa regency, and 6) find out the effect of Self Esteem and Self Regulation on the students’ Mathematic learning outcome of the eleventh grade students of Senior Islamic High School Guppi of Samata, Gowa regency. The research used Ex-postfacto method with double paradigm research design. The population of this research was all the students of the eleventh grade of Senior Islamic High School Guppi of Samata, Gowa regency which consisted of 55 students while the sample was 48 students by using random sampling technique. The Data were analyzed by using descriptive and inferential statistics by using simple regression analysis and double regression analysis. The research findings showed that there was the effect of Self Esteem and Self Regulation on the students’ Mathematic learning outcome of the eleventh grade students of Senior Islamic High School Guppi of Samata, Gowa regency.